Pengembangan LKPD Berbasis Project Based Learning (PJBL) untuk Melatih Kemampuan Kolaborasi Peserta Didik pada Materi Perubahan Lingkungan di Mas Al-Jihad Pontianak - Tasya Yulinda; Nawawi Nawawi; Herditiya Herditiya (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Teaching materials are learning resources that are used to provide information that is prepared to support learning activities that are designed systematically and contain material on learning methods and testing or assessment options that help achieve the expected goals. The aim of this research is to determine the validity and practicality of Project Based Learning (PjBL)-based LKPD to train students' collaboration skills on environmental change material at Mas Al-Jihad Pontianak. This research uses the R&D (Research and Development) method with the ADDIE model which consists of Analyze, Design, Development, Implementation and Evaluation. The research results show that the average results from material and media experts are 91.16% with very valid criteria, the average of student and teacher response questionnaires is 95.67% with very practical criteria, so that the LKPD is based on Project Based Learning (PjBL ) to train students' collaboration skills on environmental change material, the project results were assessed at 82.85% with the criteria being very suitable for use as teaching material in the classroom learning process. Meanwhile, the collaboration questionnaire showed an average result of 63.70% with practical criteria to use.